Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Pada Bagian Riset Pemasaran dan Pusat Pelayanan Pelanggan PT. Petrokimia Gresik) - Shinta Dewi Larasati; Satrio Agung Wicaksono; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Marketing Research and Customer Service Center PT. Petrokimia Gresik is a division in PT. Petrokimia Gresik and under the Department of Promotion and Marketing Planning. Marketing Research and Customer Service Centers have 4 business processes, including customer satisfaction measurement, customer complaint services, market research and market segmentation research. In running a business process, Marketing Research and Customer Service Center often does not meet the specified time targets that hinder other business processes. It need a time scale for a business process cycle to know the time it takes to reach the target activity, the data for business process interests is not well documented. So, should be done analysis and modeling business processes that are expected to provide business process recommendation for more effective, efficient, adaptive. This study uses the Business Process Improvement Framework from phase 1: organizing improvements to phase 3: streamlining. From the business process conducted by the simulation result, which is the average time difference in the business process of the measurement of customer satisfaction 9 days 9 hours 54 minutes 43 seconds. Then all token targets are met on the business process recommendations. So, can be concluded that business processes recommendation are more efficient than the current business processes on the Marketing Research Division and Customer Service Center PT. Petrokimia Gresik.